Exploring the scientific underpinnings of investigating safety signals: analytical insights in deciphering drug safety evidence - Hammad, Tarek A.; Davis, Simon; Afsar, Salman (Frontiers in Drug Safety and Regulation, 2024)
Ensuring the safety of drugs is a critical aspect of healthcare. Accurate interpretation of drug safety evidence is vital to understand the safety profile and to evaluate the benefits and risks of the medicinal product. However, validity of this evidence has numerous challenges that must be carefully considered, highlighting the need for a heightened appreciation of data interpretation pitfalls. This paper aims to delve into the intricacies of analytic considerations in drug safety data interpretation aiming at providing insights into the safety profile of pharmaceutical interventions. The applicability of these analytic considerations extends to controlled and observational data as well as spontaneously reported individual case reports. Increasing the understanding of scientific underpinnings of evidence interpretation empowers Pharmacovigilance professionals to grasp fundamental concepts, use appropriate terminology, engage in meaningful discussions with colleagues conducting analyses, and critically evaluate evidence. These skills and knowledge enable them to make informed decisions and enhance their expertise in drug safety. By correct utilization of analytic approaches while appreciating their strengths and limitations, one can advance drug safety and benefit-risk research using evidence-based decision-making and ultimately ensure better healthcare outcomes for patients.